The Itsy bitsy spider - Trapani, Iza ([Charlesbridge Publ.], 1993)
In this expanded version of a popular song, the itsy-bitsy spider's climbing is interrupted by a fan, a mouse, a cat, and some dew before she makes her way to the top of a tree to spin her web.